An Evaluation of the Quality Assurance System for Basic Education Standards in Light of National Education Standards and National Integration - Dimas Prayanto Pratama; Muhammad Rafi Al Ghifari; Ahmad Zainuri; Frika Fatimah Zahra (Universitas Dehasen Bengkulu, 2026)
This study aims to evaluate the quality assurance system in primary education as reviewed from the National Education Standards and the integration of Islamic values in its implementation. Quality assurance is an important aspect in improving the quality of education, especially at the primary level as the foundation for developing students' character and competencies. The method used in this study is a qualitative approach with data collection techniques through observation, interviews, and documentation studies. The results show that the implementation of the quality assurance system has referred to the National Education Standards; however, there are still several obstacles in the consistency of implementation and supervision. The integration of Islamic values in the educational process contributes positively to shaping students' character to be noble, disciplined, and responsible. Therefore, it is necessary to strengthen the synergy between national standards and Islamic values in order to create an education system that is not only academically excellent but also moral and character driven